INFLUENCE OF BEHAVIORAL PHENOTYPING ON THE DEVELOPMENT OF PATHOLOGICAL CHANGES IN THE SALIVAL GLANDS OF RATS AGAINST THE BACKGROUND OF OBESITY AND STRESS - Chyzhanska, Y.O.; Slobodinyk, N.M.; Omelchenko, A.Ye.; Neporada, K.S. (World of Medicine and Biology, 2021)
Pathological changes in rat salivary glands depending on behavioral phenotyping were analyzed in a model of glutamate-induced obesity and the combined effects of obesity and stress. The study found that under conditions of modeling immobilization stress and the combined effects of obesity and stress, probable changes in the concentrations of thiobarbituric acid reactants, oxidative modified proteins and catalase in the salivary glands of stress-resistant and non-stress-resistant rats compared to controls. A probable difference between the studied parameters in the salivary glands is observed between rats with different stress resistance only in the content of thiobarbituric acid reactants. Thus, under conditions of glutamate-induced obesity and chronic stress in the salivary glands of rats with different behavioral phenotyping, a significant increase in the number of thiobarbituric acid reactants, an increase in oxidative modified proteins and a decrease in catalase activity, indicating a decrease in antioxidant system activity.
Keywords: stress resistance; oxidative stress; sodium glutamate